Studies on aspects of the physiology and pathophysiology of pancreatic polypeptide - Sive, Alan Avrom (Division of Endocrinology and Diabetology, 2017)
Pancreatic polypeptide (PP) is a 36 amino-acid residue peptide which has recently been recognised in pancreatic endocrine cells. Although PP has a number of effects on gastrointestinal and pancreatic exocrine function, its physiological function has not been clarified. Studies were undertaken to elucidate four aspects of the physiology and pathophysiology of this candidate hormone. Firstly, factors affecting the release of human PP (hPP) were assessed in healthy subjects; secondly polyacrylamide gel electrophoresis was used to investigate molecular heterogeneity of the peptide; thirdly, the organ uptake and half-life time of endogenous PP was measured in pigs; and finally, basal and stimulated serum hPP concentrations were assayed in patients with acute pancreatitis, chronic pancreatitis and maturity-onset diabetes mellitus.